Experimental investigation of transient melting and heat transfer behavior of nanoparticle-enriched PCM in a rectangular enclosure. (August 2018) - Bashar, Mohammad; Siddiqui, Kamran
Highlights: Investigated the transient melting and associated heat transfer in nanoparticle-enriched PCM in a rectangular enclosure. Four types of nanoparticles were considered among them silver and copper oxide nanoparticles showed best performance. 6% CuO fraction provides the best thermal performance, which was about 25% higher than that for the plain PCM case. Abstract: An experimental study was conducted to investigate the transient melting and heat transfer behavior of nanoparticle-PCM mixtures in a rectangular enclosure. Four types of nanoparticles, silver, copper oxide, aluminum oxide and multi-walled carbon nanotubes were considered, and paraffin wax was used as the PCM. The results show that all four nanoparticle-enriched PCM mixtures provided better thermal performance as compared to the case with the plain PCM. It has been argued that the addition of surfactant to improve the suspension-ability of nanoparticles in the PCM counteracted the viscosity enhancement due to nanoparticles in the PCM. Among the four tested nanoparticles, silver nanoparticles were found to be the most effective in the heat transfer enhancement, followed by copper oxide nanoparticles. The performances of aluminum oxide and MWCNT were hampered due to their higher settlement rates. The transient heat transfer coefficients for all cases were computed and found to have increased rapidly in the early stages of melting up to the melted fraction of about 0.2, after that they remained almost constant for the rest of the melting process. The heat transfer coefficients for CuO and silver were found to be about 18% and 14% higher than the plain PCM case, while aluminum oxide and MWCNT were lower and closer to the plain PCM case due to higher sinking rates. The thermal behavior of CuO-enriched PCM was further investigated for 1, 3, 6, 8 and 10% mass fractions of CuO. It was found that under given conditions, 6% CuO fraction provides the best thermal performance and highest melting rate. For this case, the melting rate and heat flux were about 25% higher than that for the plain PCM case.